First record of a single-clasper specimen of Pseudobatos percellens (Elasmobranchii: Rhinopristiformes: Rhinobatidae) from the Caribbean Sea, Venezuela - N. Ehemann; L. González-González (Acta Ichthyologica et Piscatoria, 2018)
Documented cases of abnormalities in elasmobranchs worldwide are more often reported for sharks than their close relatives, the skates and rays. This report confirms the occurrence of a chola guitarfish, Pseudobatos percellens (Walbaum, 1792), caught off Margarita Island, Venezuela, showing morphological abnormalities on the right side of the body, including the absence of one clasper. This is the first record of an anomalous single-clasper case in the Caribbean Sea region.